Design and Developement Multimedia Animation Corrosion and Coating Process - Sukrawan, Yusep; Permana, Enda; Komaro, Mumu; Solehudin, Agus (INVOTEC, 2018)
The purpose of this research is to create an animation-based learning media of corrosion processes in the subject of corrosion and coating. The media produced is a learning media program in the form of .swf file that can be directly installed and accessed on personal computer. This development research (RD) was started with concept exploration to find out the necessary product model, followed by its development through many test steps (expert judgment, limited test, and application test) and correction procedure until the proper product was determined.Â  The last step was an experimental process to validate the product. The research has result an animation-based interactive media which has good criteria according to the media expert judgment value of 78.3 %, studentsâ€™ response of 83.0 % and subject matter expert judgment value of 89.0 %. Validity test show that the media has a significant effect to increase a number of students who reach minimum standard competency.